Primary Soil Formation And Dynamics Of The Evolutional Transformation Of Minerals Under Action Of Living Matter - V., Mukhomorov; L, Anikina; T, Zvereva (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2016)
We present the results of a comprehensive study of soil-forming processes under the influence of a long-term and end to end (7.5 years; twenty three vegetations) cultivating of the plants on initially lifeless mineral substrates (crushed granite, zeolite) under controlled conditions. The data were obtained under regulated conditions. It was shown that the higher plants (tomato, spring wheat) can actively participate in the pedogenesis process. We analyzed the evolutionary dynamics of the accumulation of organic matter and the dynamics of the biotic community. The result of the biogenic weathering minerals is decomposition of the rock, washing-out of the mineral elements, transformation of the minerals, formation of a secondary minerals and melkozem. We give consideration of the evolutionary dynamics of the chemical composition of plant tissues (roots, stems, leaves and reproductive organs). It was analyzed the percentage of the plant tissues the following chemical elements: P, S, Cl, Ca, Mg, Na, K, Fe, Si, Al, Mn, Zn. It was used the information approach for a quantitative analysis of the interrelation dynamics of changes in the chemical composition of the mineral substrates and chemical composition of plant tissues. The chemical composition of the mineral substrate evolutionary changes so that it is close to the information content of the plant root system. Studies processes of accumulation and transformation of the organic matter in the mineral substrate have shown that in a very short period of time under conditions of intense year-round cultivation of plants in the mineral substrates occur an intensive their enrichment by organic substance.